Eficiência de mix de plantas de cobertura em função da taxa de semeadura - Pletsch, Fernando (2024)
In the no-till system, it is recommended that soil disturbance be limited to the planting furrow, crop rotation be practiced, and the soil be permanently covered by residues of commercial crops or cover crops. Cover crops provide a range of benefits, such as soil coverage through their straw, which minimizes erosion risks, contributes to improvements in the biological, physical, and chemical characteristics of the soil, enhances porosity and nutrient cycling, and easily fits into rotation due to their diversity and cultivation flexibility. The addition of dry mass in both quantity and quality is fundamental for the no-till system, and thus, the use of cover crop mixes is gaining ground as they meet these objectives. However, little is known about the efficiency behavior of dry mass production in different seeding rates of consortia. The objective was to find the point of maximum technical efficiency of dry mass production and the efficiency of dry mass production per kilogram of seed used in seeding, as well as to evaluate the efficiency of the intercropped species compared to single species. The experiment was conducted in the experimental area of the Federal University of Technology - Paraná, Dois Vizinhos campus. The experimental design was randomized blocks with three replications, testing 8 treatments, consisting of 4 mixes (310M, 310S, 410M, 410S) derived from combinations of winter cover crops, black oat (Avena strigosa), rye (Secale cereale), common vetch (Vicia sativa), and forage radish (Raphanus sativus), and the same species in single cultivation to compare the efficiency of dry mass production per kilogram of seed in both single and intercropped cultivation. The plots measured 24x1.55 m and the subplots 6 m in length and 1.55 m in width, where seeding rates of 60%, 100% (configured/recommended rate), 140%, and 180% were tested, totaling 32 subplots in each block and a final total of 96 plots. Dry mass assessment was performed by collecting 1.5 linear meters (0.25 m²) in each subplot, followed by botanical separation of the species in the mixes to estimate the contribution of each to the total dry mass. Canopy closure assessments were also conducted using the SISCOB program. Soil cover by the aerial canopy is higher at the higher rates in assessments closer to emergence, leveling off at the end of the cycle. Efficiency is greater with the use of lower seeding rates; however, dry mass production is higher with the use of higher rates.